THE RELATIONSHIP BETWEEN METACOGNITION SKILLS WITH THE STUDENT’S ACHIEVEMENT: THE IMPLEMENTATION OF READING-CONCEPT MAP-THINK PAIR SHARE (REMAP TPS) MODEL - Linda Tri Antika (JURNAL PENA SAINS, 2018)
The objectives of this study were: 1) to explain the correlation of metacognitive skills and students achievement taught using Reading-Concept Map-Think Pair Share, and 2) to explain the contribution of metacognitive skills to students achievement. This study used correlational research design. Subjects of this research were the 10th-grade MIA-2 students at SMAN 2 Malang. This study was done in one semester. The results of the study showed that: 1) there was a significant correlation between metacognitive skills and students achievement, and 2) the contribution of metacognitive skills to students achievement was 79,6% %.